The quadratic equation is given by y = -2x² + 4x + 1
The standard form of a quadratic equation is given by:
y = ax² + bx + c
At point (1, 3):
3 = a(1)² + b(1) + c
a + b + c = 3 (1)
At point (2, 1):
1 = a(2)² + b(2) + c
4a + 2b + c = 1 (2)
At point (-2, -15):
-15 = a(-2)² + b(-2) + c
4a - 2b + c = -15 (3)
Solving equations 1, 2 and 3 simultaneously gives:
a = -2, b = 4, c = 1
The quadratic equation is given by y = -2x² + 4x + 1
Find out more on quadratic equation at: https://brainly.com/question/1214333